The power and pain of words: how language matters in responding to patients after harm - Benjamin, E. M.; Peterson, A.; Schweitzer, L.; Calcasola, S.; Korn, F.; Lodato, P.; Bradley, J.; Hemmelgarn, C. (Frontiers in Health Services, 2025)
A change is slowly occurring in the ways healthcare responds to patients after they experience harm. The imperative to be transparent with patients and families has been accepted as a key element of high quality, safe and patient-centered healthcare. The language used to describe the experience of the people impacted by harm events is also evolving, recognizing that certain words can help or hinder the experience of patients affected by harm. The language describing these efforts is shifting from legal and institutional terminology to more inclusive terms recognizing broader groups impacted by harm. We describe the evolution of language regarding harm response and make recommendations for the future of the field. While our observations on language are specific to the terminology used in the United States, the concept of moving to more patient-centered language is universal. Other countries should make similar reviews to use more patient-centered language when discussing patient harm.